Influence of meteorological elements on behavioral responses of gir cows and effects on milk quality - Silva, Marcos Vinícius da (2021)
This study aimed to analyze the principal components of the meteorological variables, physiological and behavioral response of cows subjected to different cooling times and their influence on milk quality, in the dry and rainfall periods, and to establish multiple regression models for milk quality. The data used in the study came from an experiment conducted in the Agreste Region of Pernambuco. The pre-milking cooling time was 10, 20, 30 min. and the control (without cooling). Sixteen multiparous lactating Gir cows were selected. Data were analyzed by principal component analysis and a multiple regression analysis was applied to determine milk quality. There was a strong relationship between somatic cell count (SCC) and activity of the animal in the shade for dry, and lying for rainfall, with increased SCC in cow milk. It was possible to establish two multiple regression models to determine milk quality in dry and rainfall periods. According to the principal component analysis, the cooling time to meet the thermal requirement of the animals was 20 min., regardless of the season and milking shift.